2021
DOI: 10.1002/edm2.220
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare experience among patients with type 2 diabetes: A cross‐sectional survey using the IEXPAC tool

Abstract: Aim To assess the experience with health care among patients with type 2 diabetes (T2DM) and to evaluate patients’ demographic variables and healthcare‐related characteristics which may affect their experience. Methods A cross‐sectional survey was delivered to T2DM adults. Patient experiences were assessed with the ‘Instrument for Evaluation of the Experience of Chronic Patients’ (IEXPAC) questionnaire, a validated 12‐item survey, which describes patient experience within the last 6 months (items 1–11) and hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 25 publications
(27 reference statements)
1
4
0
Order By: Relevance
“…Finally, the experience of patients regarding the health care attention received, evaluated with the IEXPAC tool, showed that there was opportunity for improvement for both groups, without significant differences. Similar results have been previously obtained regarding the information that patients receive or can access [19,37].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Finally, the experience of patients regarding the health care attention received, evaluated with the IEXPAC tool, showed that there was opportunity for improvement for both groups, without significant differences. Similar results have been previously obtained regarding the information that patients receive or can access [19,37].…”
Section: Discussionsupporting
confidence: 89%
“…The overall score of the 11 questions is calculated as their average score and ranges from 0 to 10. The additional question (item 12) is reported separately and ranges from 0 to 10 [ 19 , 37 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results also reinforce the importance of seeking a triple goal [23] in healthcare focused on improving the patient experience and population health (specially through the improvement of the relationship between health care professionals and patients) [24,25], reducing the per capita cost of human-centered care, optimizing resources and making the use of new technologies essential. A recent publication about the healthcare experience of Spanish patients with T2DM also highlights the importance of a good healthcare professional-patient relationship, based on emotional links and interpersonal trust, with regular follow-up by the same physician and involvement of nursing to improve diabetes management [26].…”
Section: Discussionmentioning
confidence: 99%
“…After conducting a literature review, a total of 10 instruments were selected. For instance, IEXPAC [ 18 ] evaluates the chronic patient experience in terms of the use of technological solutions, educational empowerment, and self-management, which is useful to evaluate the acquisition of skills of admitted patients and the trust of selected devices; PES-Q [ 16 ] evaluates patients’ empowerment and acceptance of the solution; SUS [ 19 ] is traditionally used to evaluate the usability of digital systems. These were examined with 10 professionals during a discussion session.…”
Section: Methodsmentioning
confidence: 99%